Deformation behavior of high-entropy oxide (Mg, Co, Ni, Cu, Zn)O under extreme compression. (October 2022) - Yue, Binbin; Dai, Wenhao; Zhang, Xiaoliang; Zhang, Hengzhong; Zhong, Wei; Liu, Baochang; Kawaguchi, Saori; Hong, Fang
Abstract: Following the discovery of high-entropy alloys, high-entropy oxides have gained considerable interest due to their unconventional structural characteristics and versatile functional properties for promising applications. Via synchrotron radial x-ray diffraction in a diamond anvil cell, the mechanical strength and deformation behavior of a typic high-entropy oxide (Mg, Co, Ni, Cu, Zn)O with a rock-salt structure under extreme compression has been investigated in situ . This compound in a polycrystalline state shows a large elastic anisotropy at the initial compression stage and then gradually becomes isotropic at around 21.4 GPa, similar with the behavior of MgO. Based on the lattice strain order conversion and texture evolution under compression, a dominant slip system transition from {100}<011> to {110}<1–10> is proposed in this high-entropy oxide. This work deepens our understanding on the role of chemical disorder in the mechanical properties of entropy-stabilized oxides, which would be indispensable to the design of advanced structural ceramics with optimal strength-to-ductility ratio. Graphical abstract: Image, graphical abstract